Acinetobacter baumannii Strains Deficient in the Clp Chaperone-Protease Genes Have Reduced Virulence in a Murine Model of Pneumonia - Belisario, J Christian (Pathogens, 2021)
Acinetobacter baumannii has emerged as a significant opportunistic Gram-negative pathogen and causative agent of nosocomial pneumonia especially in immunocompromised individuals in intensive care units. Recent advances to understand the contribution and function of A. baumannii virulence factors in its pathogenesis have begun to elucidate how this bacterium interacts with immune cells and its interesting mechanisms for multi-antibiotic resistance. Taking advantage of the availability of the A. baumannii AB5075 transposon mutant library, we investigated the impact of the A. baumannii Clp genes, which encode for a chaperone-protease responsible for the degradation of misfolded proteins, on bacterial virulence in a model of pneumonia using C57BL/6 mice and survival within J774.16 macrophage-like cells. Clp-protease A. baumannii mutants exhibit decreased virulence in rodents, high phagocytic cell-mediated killing and reduced biofilm formation. Capsular staining showed evidence of encapsulation in A. baumannii AB5075 and Clp-mutant strains. Surprisingly, clpA and clpS mutants displayed irregular cell morphology, which may be important in the biofilm structural deficiencies observed in these strains. Interestingly, clpA showed apical-like growth, proliferation normally observed in filamentous fungi. These findings provide new information regarding A. baumannii pathogenesis and may be important for the development of therapies intended at reducing morbidity and mortality associated with this remarkable pathogen.